(untitled) (Journal of Asian Development Studies, 2024)
This qualitative research study examines the multifaceted impact of training programs on educational performance within educational institutions, focusing on the Layyah district. The study sample consists of ten secondary school teachers selected from different schools in the Layyah district. Through thematic analysis of key themes, including improved instructional strategies, improved classroom management, technology integration, increased collaboration among educators, implementation challenges, and success factors, essential insights are uncovered to optimize the effectiveness of training initiatives. The findings highlight the importance of a culture of continuous learning among teachers, supported by clear communication, strong leadership, and comprehensive support. Furthermore, for successful implementation, embracing technology integration and addressing challenges such as resistance to change and resource limitations is essential. Recommendations include allocating adequate resources, promoting collaboration, embracing technology integration, and providing ongoing support mechanisms. Emphasis is also placed on continuous monitoring and evaluation of training programs to ensure alignment with changing needs and maximize impact on teaching performance and student outcomes. This study provides practical guidance to educational institutions seeking to improve teaching effectiveness through targeted training initiatives, ultimately benefiting teachers and students.